Efficacy of pulmonary surfactant with budesonide in premature infants: A systematic review and meta-analysis - Nanthida Phattraprayoon; Bing Tan; Mingkwan Na Takuathung (PLoS ONE, 2025)
Pulmonary surfactant (PS) is one of the main treatment for neonates with respiratory distress syndrome (RDS). Budesonide has recently been studied as an additional treatment in such cases, but there is limited evidence supporting this. This study was implemented to determine the efficacy of PS combined with budesonide in premature infants. To achieve this, we conducted a systematic review and meta-analysis of randomized controlled trials by searching PubMed, Scopus, Embase, and the Cochrane Library from inception until July 12, 2024. We utilized a random-effects model to calculate the risk ratio and mean differences (MDs) with 95% confidence intervals (CIs) for the clinical outcomes of PS with budesonide versus PS alone. We used the GRADE approach to assess the quality of the evidence. We included 26 randomized controlled trials with a total of 2701 patients in the analysis. Treatments of PS with budesonide and PS alone were compared in all trials. PS with budesonide reduced bronchopulmonary dysplasia (BPD) incidence (risk ratio, 0.61; 95% CI, 0.51, 0.73), duration of mechanical or invasive mechanical ventilation (MD, −2.21 days; 95% CI, −2.72, −1.71), duration requiring oxygen (MD, −5.86 days; 95% CI, −8.44, −3.29), and hospitalization time (MD, −5.61 days; 95% CI, −8.65, −2.56). These results were based on low to very low evidence certainty. Only moderate-to-severe BPD or severe BPD showed a significant reduction when PS was used in conjunction with budesonide, a finding supported by moderate evidence certainty. Our study showed that the administration of PS with budesonide significantly improved respiratory outcomes, including the incidence of BPD, duration of mechanical or invasive mechanical ventilation, duration requiring oxygen, and hospitalization time in preterm infants, without short-term adverse drug events. However, the evidence certainty was mostly low to very low.